Using The Development Life Cycle (SDLC) System As A Retail Sales Information System - Prihatiningsih, Tri; Suhandini, Yustina; Santikai, Dewi (Universitas Panca Marga, 2023)
This study aims to solve problems experienced at the Six Store Probolinggo Store where data recording and investigation of sales and purchase transactions still use manual goods receipts. When checking the size or stock of goods for each product when purchasing at offline user sales, the user still has to wait to find out whether stock is still there or not and the high error rate that occurs.The Six Store store needs a way to solve the problems that occur, so the researchers created a system design using the System Development Life Cycle (SDLC) method. This method was chosen because SDLC can measure and improve the sales process more effectively, minimize operational costs and increase revenue throughout the day. While programmers use VB 6.0-based applications and Ms. Access. It can be concluded if there is progress produced by the news system. This proves that regular financial bookkeeping can affect the results of the sale itself.This News System is able to obtain sales reports per note, per item variant, per item and inventory reports in such a short time according to user needs. The results of the application of the Information System show an increase in turnover of 75% every year at the Six Store Probolinggo Store.